Atrial arrhythmias in Takotsubo cardiomyopathy: incidence, predictive factors, and prognosis. Issue 2 (10th July 2018) - Jesel, Laurence; Berthon, Charlotte; Messas, Nathan; Lim, Han S; Girardey, Mélanie; Marzak, Halim; Marchandot, Benjamin; Trinh, Annie; Ohlmann, Patrick; Morel, Olivier
Abstract: Aims: Takotsubo cardiomyopathy (TTC) is a stress-related transient cardiomyopathy. It is unclear whether TTC is associated with poorer prognosis when atrial arrhythmia (AA), atrial fibrillation or flutter, occurs. The purpose of this study was to assess the incidence of AA in patients with TTC, predictive factors of AA, and its association with mortality. Methods and results: We studied 214 consecutive cases of TTC over 8 years. The study cohort was divided into two groups—those with newly diagnosed AA (AA-group) and those without (non-AA group). AA occurred in 24.8% of the patients. The AA group presented with lower left ventricular ejection fraction (LVEF) on admission and higher cardiac arrest rate. Admission and peak levels of troponin, B-type natriuretic peptide (BNP), C-reactive protein (CRP), and leucocytes were higher in the AA group. In-hospital, 30-day, cardiovascular, and all-cause mortality were significantly higher in the AA group. Independent predictors of newly diagnosed AA were troponin peak [odds ratio (OR) 1.03 (1.003–1.06); P  = 0.029], CRP peak [OR 1.006 (1.001–1.01); P  = 0.026], and LVEF on admission [OR 0.96 (0.93–0.99); P  = 0.01]. Newly diagnosed AA was not predictive of mortality. The BNP peak [OR 1.00 (1.000–1.001); P  = 0.022] and leucocytes peak [OR 1.095 (1.034–1.16); P  = 0.002] were predictive factors of in-hospital mortality. LVEF upon discharge [OR 0.935 (0.899–0.972); P  = 0.001] and leucocytes peak [OR 1.068 (1.000–1.139); P  = 0.049] were predictive of cardiovascular death. Conclusion: Newly diagnosed AA is frequently observed in patients presenting with TTC and is associated with poorer short- and long-term prognosis. Inflammation, myocardial damage, and LVEF are predictors of AA onset and cardiovascular mortality.